2018
DOI: 10.1007/s10640-018-00306-7
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth Effects of Alternative Climate Change Impact Channels in Economic Modeling

Abstract: Despite increasing empirical evidence of strong links between climate and economic growth, there is no established model to describe the dynamics of how different types of climate shocks affect growth patterns. Here we present the first comprehensive, comparative analysis of the long-term dynamics of one-time, temporary climate shocks on production factors, and factor productivity, respectively, in a Ramsey-type growth model. Damages acting directly on production factors allow us to study dynamic effects on fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 88 publications
1
25
0
Order By: Relevance
“…These values are higher than the 0.2% per year estimated by Acevedo [33] and the study of Moore et al [6], which found output losses for Barbados between 0.20% and 0.25% of GDP in 2050. This is because the model tracks a backlog of unrepaired damaged capital stocks, and cumulative damage increases subsequent GDP losses (see the discussion in [19]). Without anticipation, mean losses are higher still, on the order of 4% by 2050.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These values are higher than the 0.2% per year estimated by Acevedo [33] and the study of Moore et al [6], which found output losses for Barbados between 0.20% and 0.25% of GDP in 2050. This is because the model tracks a backlog of unrepaired damaged capital stocks, and cumulative damage increases subsequent GDP losses (see the discussion in [19]). Without anticipation, mean losses are higher still, on the order of 4% by 2050.…”
Section: Resultsmentioning
confidence: 99%
“…Such models predict that depreciation rate shocks will have very little effect on economic output [45,46]. In "New Keynesian" models [47], where actors may not respond rapidly to new information, or an RBC model in which actors do not take climate shocks into account [19], depreciation rate shocks can produce an effect. In the model developed in this paper, when accurately anticipated, depreciation rate shocks from climate events can be accounted for in the design of physical capital, but as noted above, expected damage may differ from realized damage, either because of the particular sequence of storm events or because the climate is changing in ways that economic actors did not anticipate.…”
Section: The Perpetual Inventory Model With Climate Damagementioning
confidence: 99%
See 2 more Smart Citations
“…However, while using the core results for the climate-induced pressures on economic growth in each year, we additionally assume that the resulting GDP losses are fully recovered in the end of each year and the economy returns to its original trajectory. Termed as level effects, this approach is known to give a more conservative estimate for climate impacts compared to growth effects, when the lost GDP is never recovered (Burke et al, 2015;Piontek et al, 2018). Current data suggests that both types of economic responses to rising temperatures are possible depending on a country's socio-economic and climatic conditions (Burke et al, 2015;Newell et al, 2018;Piontek et al, 2018).…”
Section: Resultsmentioning
confidence: 99%